Kebijakan PPDB Sistem Zonasi SMA/SMK dalam mendorong Pemerataan Kualitas Sumberdaya Manusia di Jawa Timur - Ahmad Mashudi (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2019)
This paper discusses the importance of the zoning system in the acceptance of SMA / SMK New Students (PPDB) towards the equal distribution of the quality of Human Resources (HR) in East Java Province. The zoning system in accepting high school / vocational students will prevent the accumulation of certain quality human resources in the region. Zoning of high school / vocational student admissions will encourage equal distribution of quality human resources in an area, making it easier to meet the needs of the workforce to support local economic activities. The author uses a descriptive qualitative approach in analyzing the application of zoning systems in PPDB SMA / SMK in East Java. A qualitative case study strategy was used to explain the impact of the policy in reducing disparity in human resource quality between regions in East Java. In this case, the authors use the assumption that providing equal opportunities to obtain quality education in an area will guarantee the availability of quality human resources equally. This paper presents an interesting analysis, that the direct or indirect PPDB zoning system policies at the SMA / SMK level will encourage even distribution of quality human resources in East Java. First, the high school / vocational PPDB zoning policy avoids the accumulation of high-quality prospective students in only one particular school in a particular region, thus raising exclusivity in the field of education. Second, the implementation of the zoning system policy guarantees the availability of quality workforce equally, because students receive teaching by teachers and educational resources with no different quality. The absence of a gap in the quality of graduates will ultimately increase the even distribution of quality human resources in all regions of East Java.